2017
DOI: 10.1111/maps.12899
|View full text |Cite
|
Sign up to set email alerts
|

Ultra‐reduced phases in Apollo 16 regolith: Combined field emission electron probe microanalysis and atom probe tomography of submicron Fe‐Si grains in Apollo 16 sample 61500

Abstract: The lunar regolith contains a variety of chemically reduced phases of interest to planetary scientists and the most common, metallic iron, is generally ascribed to space weathering processes (Lucey et al. 2006). Reports of silicon metal and iron silicides, phases indicative of extremely reducing conditions, in lunar samples are rare (Anand et al. 2004;Spicuzza et al. 2011). Additional examples of Fe-silicides have been identified in a survey of particles from Apollo 16 sample 61501,22. Herein is demonstrated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 41 publications
(82 reference statements)
0
21
0
Order By: Relevance
“…Much of what is known about space weathering products was realized through the study of lunar samples. Based on lunar sample studies, one of the primary metallic byproducts of space weathering is iron metal (Keller & McKay, ; Keller & McKay, ; Noble et al, ; Taylor et al, ), although iron silicides (e.g., hapkeite) and rare metallic Si also make up a minor fraction of metallic space weathering products (Anand et al, ; Gopon et al, ). The iron metal produced through space weathering occurs along a continuum of nanophase iron particles that coarsen through Ostwald ripening to larger particles (Lucey & Noble, ; Noble et al, ; Pieters et al, ; Pieters & Noble, ).…”
Section: Secondary Processes That Could Have Affected the O/si Ratio mentioning
confidence: 99%
See 2 more Smart Citations
“…Much of what is known about space weathering products was realized through the study of lunar samples. Based on lunar sample studies, one of the primary metallic byproducts of space weathering is iron metal (Keller & McKay, ; Keller & McKay, ; Noble et al, ; Taylor et al, ), although iron silicides (e.g., hapkeite) and rare metallic Si also make up a minor fraction of metallic space weathering products (Anand et al, ; Gopon et al, ). The iron metal produced through space weathering occurs along a continuum of nanophase iron particles that coarsen through Ostwald ripening to larger particles (Lucey & Noble, ; Noble et al, ; Pieters et al, ; Pieters & Noble, ).…”
Section: Secondary Processes That Could Have Affected the O/si Ratio mentioning
confidence: 99%
“…products (Anand et al, 2004;Gopon et al, 2017). The iron metal produced through space weathering occurs along a continuum of nanophase iron particles that coarsen through Ostwald ripening to larger particles (Lucey & Noble, 2008;Noble et al, 2007;Pieters et al, 2000;Pieters & Noble, 2016).…”
Section: Journal Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…) and Apollo 16 sample 61500 (Gopon et al. ) indicates that space weathering products are not necessarily nanoscale in grain size. They could be large up to tens of micrometers (Anand et al.…”
Section: Introductionmentioning
confidence: 99%
“…Besides npFe 0 , recently, Gu et al (2018) reported the presence of silicon oxide nanoparticles (10-25 nm in grain size) in Apollo 15 lunar soil. Although typical space weathering products are on nanometer scale, the discovery of hapkeite (Fe 2 Si) in lunar meteorite Dhofar 280 (Anand et al 2004) and Apollo 16 sample 61500 (Gopon et al 2017) indicates that space weathering products are not necessarily nanoscale in grain size. They could be large up to tens of micrometers (Anand et al 2004).…”
Section: Introductionmentioning
confidence: 99%